2016
DOI: 10.1016/j.meatsci.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Natural antioxidants as food and feed additives to promote health benefits and quality of meat products: A review

Abstract: Fresh and processed meats offer numerous nutritional and health benefits and provide unique eating satisfaction in the lifestyle of the modern society. However, consumption of red meat including processed products is subjected to increasing scrutiny due to the health risks associated with cytotoxins that potentially could be generated during meat preparation. Evidence from recent studies suggests free radical pathways as a plausible mechanism for toxin formation, and antioxidants have shown promise to mitigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
267
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(293 citation statements)
references
References 137 publications
3
267
0
23
Order By: Relevance
“…For this reason, the food industry, by improving the preparation of the products and by using antioxidants, is trying to prevent and slow down the process of deterioration, in order to offer the consumer a safer deadline for use, which guarantees the quality of the food product [76][77][78][79][80].…”
Section: Flavonoids -From Biosynthesis To Human Health 206mentioning
confidence: 99%
“…For this reason, the food industry, by improving the preparation of the products and by using antioxidants, is trying to prevent and slow down the process of deterioration, in order to offer the consumer a safer deadline for use, which guarantees the quality of the food product [76][77][78][79][80].…”
Section: Flavonoids -From Biosynthesis To Human Health 206mentioning
confidence: 99%
“…The addition of diverse compounds with antioxidant and / or antimicrobial properties in the packaging, in the meat surface, or in the edible films or coatings may maintain product quality by retaining freshness and color or reducing lipid oxidation . Exploratory research has demonstrated the feasibility of reducing health risks associated with synthetic additives by replacing them with natural ingredients . Indeed, these replacements are well accepted by consumers, who prefer natural food additives to synthetic ones, and they are likely to figure in the future of food preservation due to their health benefits and synergies …”
Section: Introductionmentioning
confidence: 99%
“…(Mamani-Linares et al, 2014). La carne de llama es tecnológicamente apropiada para la elaboración de productos cárnicos, a los cuales se agregan diversos ingredientes alimentarios funcionales con fines organolépticos y de conservación (Jiang & Xiong, 2016).…”
Section: Introductionunclassified